A New Control Strategy for Three-Phase Shunt Active Power Filters Based on FIR Prediction - Kukrer, Osman; Komurcugil, Hasan; Guzman, Ramon; de Vicuna, Luis Garcia (IEEE-Inst Electrical Electronics Engineers Inc, 2021)
In this article, a new discrete-time control strategy for three-phase three-wire shunt active power filters (APFs) is presented, based on a mathematical model in the stationary reference frame. It involves a feedback-linearization-type approach to control the filter currents, whereby the voltage control loop is decoupled from the current control. The voltage control loop is for controlling the dc-side voltage of the pulsewidth modulation (PWM) converter, and employs a proportional-integral (PI) controller to generate the reference amplitude for the compensated grid currents. An important feature of the proposed control strategy is the compensation of the one-sampling-period delay caused by microcontroller computation using a finite impulse response (FIR) predictor. This predictor is designed to accomplish one-step-ahead prediction of the control variable, which is the PWM converter's switching function space vector. Furthermore, the FIR predictor is optimized so that the low-order harmonics in the control variable are predicted with minimal error. The proposed control strategy is analyzed to obtain the steady-state filter current error and ranges for the PI controller gains for stability. Simulation and experimental results are presented to show the effectiveness of the proposed shunt APF.
Keywords: Finite impulse response filters; Active filters; Switches; Power harmonic filters; Voltage control; Current control; Harmonic analysis; Finite impulse response (FIR) predictor; predictive control; shunt active power filter (APF)